Integrating Research Results into Decision Making about Natural Resource Management at the Forestagriculture Interface: a Case Study in the Congo Basin - Ngobo, M.; Weise, Stephan F.; Peters, M. (2004)
Unlike Southeast Asia and the Amazon regions, where large-scale agricultural operations play an important role, most of the deforestation in the Congo basin is attributed to smallholder agriculturalists using extensive slash-and-burn techniques. Improved rural livelihoods are the key to poverty reduction and sustainability of landscape mosaics at the forest-agriculture interface of the Congo basin region. The issue has become more complex with globalisation and the situation therefore calls for an innovative approach that would look at trade offs between sustainability and productivity growth. On this basis, a collaborative partnership uniting research institutes, non-governmental organisations and universities members of the Alternatives to Slash-and-Burn national Consortium in Cameroon work with local communities to identify and develop policy, institutional and technological land-use options that can improve rural livelihoods while preserving the country's remaining forests. During the first three Phases of the programme (1994 to 2003), the global objective has been to: characterise and evaluate existing land use systems; modify or develop alternative technologies to the practice of slash-and-burn cropping system; identify, assess and design policy tools and mechanisms through which they could be implemented with the aim of protecting the environment by reducing the rate of deforestation. So far, the Project main outputs include: baseline environmental, agronomic, economic, and social datasets compiled and assessed in 6 landscape mosaics of the Forest Margin Benchmark; different resource management options for increased productivity of annual crop-based systems, perennial crop-based systems, and community-managed natural resource systems tested with farmers in the benchmark area; integrative landscape-level models and participatory community action methodologies developed; local capacity built in the use and interpretation of the models and methodologies and their outputs/outcomes; and mechanisms for policy formulation and dialogue improved at the local, provincial and national levels, targeting landscape mosaic and natural resources management.From the ASB experience, it is concluded that there is no single ‘best bet' solution to rural poverty alleviation at the forest-agriculture interface of Congo basin region. Only by integrating technology development, policies and institutional innovation can the question “are sustainable landscape mosaics feasible at the forest-agriculture interface in the Congo Basin region?” be addressed objectively.